Consolidation therapy revisited: intravenous chemotherapy. (1st October 2003) - Markman, M.
Abstract : The administration of 'consolidation' therapy is designed to maximize the benefits achieved from primary chemotherapy, to both improve progression-free and overall survival. Paclitaxel is an excellent agent to consider for a consolidation strategy in ovarian cancer, based on its activity in the disease, its cycle-specificity, and the lack of serious cumulative toxicity (except for neuropathy). A recently reported randomized trial conducted by the South-west Oncology Group and the Gynecologic Oncology Group revealed that 12-monthly cycles of single-agent paclitaxel (175 mg/m 2 over 3 h) improves progression-free survival (PFS), compared to 3-monthly cycles of the agent (median PFS: 28 months versus 21 months, P = 0.0023, and hazard ratio 2.31). Further exploration of consolidation/maintenance therapy in the management of ovarian cancer is indicated, focusing on agents that are easy to administer (eg, oral) and that result in limited cumulative toxicity.